"Taking the Wanting out of the Waiting": HIV, Transactional Sex, and #Blessed in the Context of Neo-Liberal Christianity - Haddad, Beverley (Journal of theology for Southern Africa, 2018)
There are 2000 new HIV infections amongst young women between the ages of 15 and 24 in South Africa each week. Research over the past fifteen years has shown that transactional sex with older men, traditionally known as “sugar daddies”, is a key driver in this vulnerability. Recently, these older men have been termed “blessers” on social media sites with a community of young urban women, #Blessed, seeking lifestyles that embrace the commodified goods of neoliberal capitalism. The article discusses the notion of “transactional sex” and positions young women as both victim and agent in the South African context of unemployment and poverty. Possible linkages between the “blesser” phenomenon and theologies that promote prosperity “as a blessing from God” are explored. The article argues that by naming these relationships #Blessed, young women choose to harness the tools of prosperity theology and link their desire for material wealth and consumer lifestyles with the unmediated power of God who intervenes and “takes the wanting out of waiting”. African women’s theologies must, the article contends, address women’s agency that does not destabilise unequal gender relations by engaging the intersections of economics, gender, and sexuality in the current South African context.
Free